2021
DOI: 10.56294/saludcyt202137
|View full text |Cite
|
Sign up to set email alerts
|

Nursing governance in integrated health service networks and its impact on care processes in the field of primary care teams

Abstract: Introducción: gobernanza profesional constituyen los procesos y estructuras que dan a los enfermeros autonomía, control y autoridad acerca de la práctica de enfermería en una organización. Objetivo: describir la percepción de la gobernanza de enfermería en redes integradas de servicios de salud a partir del proceso de atención de enfermería en el ámbito de Equipos del Primer nivel de atención. Método: se realizó un estudio descriptivo, transeccional en junio 2020, mixto. Se estudiaron 66 trabajadores de 11 Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…Key findings are then discussed and compared with previous research, methodological limitations and errors are identified, conclusions are reached, and needs for future research are highlighted. (16,17,18,19) Regarding the relationship between aerobic exercise and mental health, studies showed that aerobic training increases plasma Cathepsin B (CTSB) enzyme levels, which correlates with improved cognitive performance. However, brain-derived neurotrophic factor (BDNF) levels decrease with exercise.…”
Section: Resultsmentioning
confidence: 99%
“…Key findings are then discussed and compared with previous research, methodological limitations and errors are identified, conclusions are reached, and needs for future research are highlighted. (16,17,18,19) Regarding the relationship between aerobic exercise and mental health, studies showed that aerobic training increases plasma Cathepsin B (CTSB) enzyme levels, which correlates with improved cognitive performance. However, brain-derived neurotrophic factor (BDNF) levels decrease with exercise.…”
Section: Resultsmentioning
confidence: 99%
“…El estudio de la escabiosis en los niños es esencial para proteger su salud y evitar la propagación de la infección. (17) En relación con lo relativo a la edad y el sexo, los estudios Izquierdo Herrera y Torres Ramírez, (18) Espinoza, (19) Aldana et al (20) , Rogel Aquino, (21) tuvieron comportamientos similares a nuestro estudio.…”
Section: Discussionunclassified
“…In the current study, it iscarried out from a public and community health perspective on the cardiovascular risks that can occur in people with high blood pressure, since it is one of the diseases considered health priorities [18][19][20][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%